LUPUS ERITEMATOSUS SISTEMIK PADA KEHAMILAN - Jaya Kusuma, Anak Agung Ngurah (journal of internal medicine, 2012)
Systemic lupus erythematosus (SLE) is an auto immune disease which is charaterized by the production of antibodies towards the nucleus of the cell. The mechanism is not well defined, but there seem to be some exacerbating factors like physical and metal stress, infection, ultraviolet radiation and drugs. The various cell of our body are recognized as antigen therefore leading to the formation of immune complexes which will be deposited in organs and eventually cause inflammation. The process which affects the placenta is known as deciduas vasculitis. The effects of pregnancy towards SLE in unclear, but the risks of exacerbation increases as pregnancy advances. Complications such as death of the fetus, premaurity and restricted growth may occur. Complication of pregnancy with SLE which affects the fetus characterized by congenital heart block, cutaneus lesion, cytopenia, liver disorders and other systemic manifestation. The pathogenesis of fetal heart block is not well understood, but the mechanism seems to be transfers of antibody through the placenta on the second trimester which then will lead to immunological trauma of the heart and its conduction system which will manifest upon delivery. There are two major points to be considered in the management of SLE in pregnancy; pregnancy can affect the course of SLE and the fetus may become the target of auto antibody which will lead to failure of the pregnancy itself. Corticosteroids have a significant effect and is normally tolerable by may be considered. Contraception becomes an important key in SLE as estrogens concentration of 20-30 urg/day may exacerbate SLE and will increase the risk of thromboemboli, therefore progesterone containing contraceptives are highly recommended.
Keywords: systemic lupus erythematosus, pregnancy, management